PENAFSIRAN KONTEKSTUAL AYAT PERANG DAN PENGAMALANNYA DALAM KONTEKS SOSIO-HISTORIS INDONESIA KONTEMPORER - Lina Aniqoh (UIN ANTASARI BANJARMASIN, 2021)
It is proven in the Qur'an that several verses textually seem to command Muslims to commit violence (qital verse). This paper attempts to elaborate on the contextual interpretation of QS Muhammad verse 4 and QS at Taubah verse 5. Two verses that extremist Islamic groups often misinterpret to legitimize their destructive acts. The interpretation is carried out using Fazlur Rahman's hermeneutical methodology, double movement. The interpretation results show that the two verses contain moral values in war. Namely, war must be reactive, use the ethics of